Mapping early social development in rodents through the lens of interpersonal synchrony - Ham, Gao Xiang (Neuroscience Singapore, 2023)
In humans, parent-child neural synchrony has been shown to support early communication, social attunement and learning. However, very little is known about the developmental origins and sequelae of neural synchrony, and whether this neural mechanism might play a causal role in the control of social and communicative behaviour across species. Rodent models are optimal for exploring such questions of causality, with a plethora of tools available for both disruption/induction (optogenetics) and even mechanistic dissection of synchrony-induction pathways (in vivo electrical or optical recording of neural activity). However, before rodent models can be leveraged to dissect parent-infant synchrony mechanisms, we first need to understand the forms of parent-pup synchrony that occur during rodent development, and their trajectory of change over time. Using longitudinal video and ultrasonic-audio recordings, we followed the naturalistic development of C57/BL6 mice families (n=5) from infancy to adolescence (postnatal day 5 to 35) in a standard home-cage environment. Focusing on behaviours with particular analogies to the human context, we quantified the duration and occurrence of various dam-pup social behaviours that could potentially drive or facilitate synchrony between dam-pup dyads. Quantified behaviours fell into 3 main categories: instrumental, social interactive and vocal communicative behaviours. Reminiscent of human social development, over time we observed a gradual reduction in the frequency of instrumental behaviours (nursing, nest building) and a concomitant increase in social interactive behaviours (allogrooming, social sniffing, social rearing and social play). Several time-specific peaks in social behaviour (maternal licking/grooming, solicitations) were also observed, potentially reflecting the occurrence of crucial social developmental periods. Further, we identified several categories of ultrasonic vocalisations (USVs) that mirrored social behavioural trends (eg. downward calls with nursing or complex calls with solicitations). Akin to human communication, these calls may represent unique social cues involved in establishing and maintaining interpersonal synchrony during successful social interactions. Our results help to elucidate the full spectrum of dam-pup social behaviours that may potentiate synchrony during rodent early development, addressing an important gap in cross-species research on neural synchrony.